2021
DOI: 10.1002/acp.3863
|View full text |Cite
|
Sign up to set email alerts
|

The difficulty of teaching adults to recognize referential ambiguity in children's testimony: The influence of explicit instruction and sample questions

Abstract: Adults often fail to recognize the ambiguity of children's unelaborated responses to “Do you know/remember (DYK/R) if/whether” questions. Two studies examined whether sample questions and/or an explicit instruction would improve adults' ability to recognize referential ambiguity in children's testimony. In Study 1 (N = 383), participants rarely recognized referential ambiguity in the sample questions or in children's testimony, and answering sample questions had no influence on their ability to detect ambiguit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…When interviewers ask “do you remember the time…” and children simply answer “no,” it will be unclear whether they don’t remember the event or merely the time. This adds to the growing evidence that “do you remember” questions in general should be avoided, both because they elicit under informative and ambiguous responses (Ahern et al, 2016; Evans et al, 2014; 2017), and because their ambiguity is overlooked by adults (Wylie et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…When interviewers ask “do you remember the time…” and children simply answer “no,” it will be unclear whether they don’t remember the event or merely the time. This adds to the growing evidence that “do you remember” questions in general should be avoided, both because they elicit under informative and ambiguous responses (Ahern et al, 2016; Evans et al, 2014; 2017), and because their ambiguity is overlooked by adults (Wylie et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…"; Evans et al, 2017). Even adults fail to recognize the ambiguity of "Do you know/ remember" questions (Wylie et al, 2019;Wylie, Gongola, et al 2021). Declarative questions are thought to be a less complex form of suggestive prompt (fewer words, fewer clauses, and fewer false starts; Henderson & Lamb, 2019), though they frequently elicit agreement rather than elaborated responding (Bishop et al, 1998;Stolzenberg et al, 2019).…”
Section: Canadian Lawmentioning
confidence: 99%
“…“Do you know/remember” questions are complex because children may fail to understand the pragmatics of the question (“Do you know what colour it was?” “Yes.” “Ok, what colour was it?”) or provide ambiguous responses (“Do you know if it was blue?” “No.” “No, you don’t know or no, it’s not blue?”; Evans et al, 2017). Even adults fail to recognize the ambiguity of “Do you know/remember” questions (Wylie et al, 2019; Wylie, Gongola, et al 2021). Declarative questions are thought to be a less complex form of suggestive prompt (fewer words, fewer clauses, and fewer false starts; Henderson & Lamb, 2019), though they frequently elicit agreement rather than elaborated responding (Bishop et al, 1998; Stolzenberg et al, 2019).…”
Section: Canadian Lawmentioning
confidence: 99%
“…Wylie et al (2019) found that adults were equally likely to interpret unelaborated ‘no’ responses as answering the implicit question (34% interpreted as ‘No, it did not happen’) and explicit question (26% interpreted as ‘No, I don't remember’), and rarely identified children's responses as being unclear (7% of the time). Wylie et al (2021) found that even when they were given an explicit instruction explaining that unelaborated responses to ‘do you remember’ questions lead to ambiguity, adults failed to recognize referential ambiguity when presented with transcripts containing ambiguous answers to ‘do you remember’ questions.…”
Section: Adult Perceptions Of Invitations Using the Word ‘Time’mentioning
confidence: 99%